34% of Delegates are Women (1976)
This July 11, 1976 press release from the Democratic National Committee outlines the profile and growing political role of women delegates at the 1976 Democratic National Convention. Key points: Representation: Women made up 34% of the 3,075 delegates in 1976. While slightly lower than the nearly 40% in 1972 (when quotas were used), this marked a significant increase from 13% in 1968, reflecting long-term progress. Background and demographics: Age: 65% were between 35–60; 28% were 18–35; 7% were over 60.Education: 87% had attended college; 27% held college degrees; 23% had advanced degrees; 9% had some graduate study. Employment: Three-fourths were employed outside the home, with teaching as the most common occupation. Others worked in a wide range of professions, from clerical and service jobs to business ownership and technical fields. Political experience and engagement: 86% were active in Democratic Party activities. 75% were attending their first national convention. 37% had run for public office (mostly state legislature), and 21% currently held public office. Ten state delegations were headed by women. The release emphasizes that although quotas were no longer permitted in 1976, women continued to gain influence through grassroots involvement and party leadership roles. Harriet Cipriani, Director of Women's Activities, expressed pride in the progress made and confidence that continued activism would lead to equal representation in future conventions.